Equation of Human Rights Principles in the Medina Charter with Human Rights Principles in the 1945 Constitution - Sri Solehah; Siti Hasanah; Firzhal Arzhi Jiwantara (al-Afkar, Journal For Islamic Studies, 2024)
This study aims to compare the equation of the principles of human rights (HAM) in two important historical documents, namely the Medina Charter and the 1945 Constitution (1945 Constitution) Indonesia. The Medina Charter, as the first social contract in Islamic history, and the 1945 Constitution, as the Indonesian constitution, has a big impact in the development and protection of human rights in each context. This study uses a document analysis method to identify and compare the principles of human rights contained in the two documents. It was found that there were a number of equations of human rights principles in the Medina Charter and the 1945 Constitution, even in different contexts. Universal principles such as freedom of religion, the right to life, and right of justice appear to be present in both documents. However, the implementation and interpretation of these principles can vary depending on differences in the context of history, culture, and politics in which these documents are produced. In addition, this research also highlighted the role and development of the concept of human rights from the Medina Charter to the 1945 Constitution. Although there are a number of changes and adjustments, it appears that human rights principles have become an integral part of the legal structure in accommodating community needs. In conclusion, although there are contextual differences between the Medina Charter and the 1945 Constitution, this research identifies the equation of human rights principles that reflect universal human values. Understanding of this equation can provide further insight about the evolution of the concept of human rights in history and how these values ​​remain relevant in the context of modern society.